The end of automobile dependence : how cities are moving beyond car-based planning - Newman, Peter, 1945-; Kenworthy, Jeffrey R., 1955- (Washington, DC : Island Press, 2015)
In this publication, Newman and Kenworthy look at how we can accelerate a planning approach to designing urban environments that can function reliably and conveniently on alternative modes. They consider a refined and more civilized automobile playing a very much reduced and manageable role in urban transportation. The authors examine the rise and fall of automobile dependence using updated data on 44 global cities to better understand how to facilitate and guide cities to the most productive and sustainable outcomes. This is the final volume in a trilogy by Newman and Kenworthy on automobile dependence (Cities and Automobile Dependence in 1989 and Sustainability and Cities: Overcoming Automobile Dependence in 1999). Like all good trilogies this one shows the rise of an empire, in this case that of the automobile, the peak of its power, and the decline of that empire.
Preface -- The Trilogy -- 1. The Rise and Fall of Automobile Dependence -- 2: Urban Transportation Patterns and Trends in Global Cities -- 3: Emerging Cities and Automobile Dependence.-4: The Theory of Urban Fabrics: Understanding the End of Automobile Dependence -- 5: Transportation Planning: Hindrance or Help? -- 6: Overcoming Barriers to the End of Automobile Dependence -- 7: The End of Automobile Dependence: A Troubling Prognosis? -- 8: Conclusion: Life after Automobile Dependence.
Online resource; title from PDF title page (EBSCO, viewed July 15, 2015).
Includes bibliographical references and index.
English.
Keywords: Urban transportation policy; Urban transportation -- Environmental aspects; Sustainable development; Land use, Urban; Automobiles -- Environmental aspects; BUSINESS & ECONOMICS -- Industries -- Transportation; TRANSPORTATION -- Public Transportation; Highway & traffic engineering; The environment; Automobiles -- Environmental aspects; Land use, Urban; Sustainable development; Urban transportation -- Environmental aspects; Urban transportation policy; Electronic books